2021
DOI: 10.1097/cm9.0000000000001787
|View full text |Cite
|
Sign up to set email alerts
|

Factors relating to bone mineral density in young and middle-aged patients with ankylosing spondylitis

Abstract: Background: Ankylosing spondylitis (AS) is a common chronic progressive rheumatic disease. The aim of this study was to explore factors influencing abnormal bone mineral density (BMD) in young and middle-aged patients with AS. Methods: From July 2014 to August 2018, hospitalized patients with AS and health examinees in the health examination center of our clinics, ranging in age from 20 to 50 years, were monitored. The BMD of the lumbar spine and femoral neck of AS pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…There are some shortcomings in the present study, including (1) This study lacks the transportation used by patients, which only investigated the distance between primary hospitals and the city center; (2) Patients receiving non-steroidal anti-inflammatory drugs and sulfasalazine is not included in this study due to difficulties in obtaining information about their previous medication; (3) Due to inadequate training of primary hospitals' doctors in AS history collection, physical examination, and condition assessment, information about AS characteristics is incomplete in this study; (4) The current evaluation indicators of this study are incomprehensive and less convincing to reflect the diagnosis and treatment level of primary hospitals' doctors, the diagnostic accuracy rate, treatment efficiency, and other indicators should be included for comprehensive evaluation.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…There are some shortcomings in the present study, including (1) This study lacks the transportation used by patients, which only investigated the distance between primary hospitals and the city center; (2) Patients receiving non-steroidal anti-inflammatory drugs and sulfasalazine is not included in this study due to difficulties in obtaining information about their previous medication; (3) Due to inadequate training of primary hospitals' doctors in AS history collection, physical examination, and condition assessment, information about AS characteristics is incomplete in this study; (4) The current evaluation indicators of this study are incomprehensive and less convincing to reflect the diagnosis and treatment level of primary hospitals' doctors, the diagnostic accuracy rate, treatment efficiency, and other indicators should be included for comprehensive evaluation.…”
mentioning
confidence: 86%
“…In China, the prevalence of AS is about 0.29% with a male to female ratio of approximately 3:1, and most cases occur in the adolescent period. [ 1 ] The misdiagnosis rate of AS patients in China is >50%, and the average delay time of diagnosis is >7 years. Without standardized treatment, the 3-year disability rate of AS patients can reach 45.5%, and the 5-year disability rate can reach 70%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on the mechanism of LBMD caused by AS have focused on immunity and inflammation. There was a significant correlation between LBMD and bone turnover markers, osteoprotegerin, proinflammatory cytokines, and acute phase reactants such as CRP and ESR in AS patients, suggesting that inflammatory mediators may be involved in the pathogenesis of LBMD in AS (Kim et al, 2006;Ranganathan et al, 2017;Wu et al, 2021;Rademacher et al, 2022). It has been demonstrated that cytokines, such as IL-6 and TNF, play a vital role in AS inflammation and may be involved in bone destruction in AS (Lee et al, 2022;Rademacher et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Ankylosing spondylitis (AS) is a chronic spondyloarthropathy that occurs frequently in adolescents, with insidious onset and relapsing nature, characterizing irreversible pathological progressive disease from inflammation, bone destruction to the formation of new bone [ 1 , 2 ]. Bone formation may occur in parallel with bone mineral content loss in AS [ 3 , 4 ]. Syndesmophyte formation and progressive ankylosis as well as fracture caused by bone loss are main causes of disability.…”
Section: Introductionmentioning
confidence: 99%